(untitled) (Research, Society and Development, 2024)
Objective: The present study seeks to review the literature regarding the effectiveness of using articaine in different anesthetic techniques in pediatric dentistry patients, in order to support its applicability for use by dentists regarding the appropriate choice of anesthetic salt and techniques to be used. Methodology: This is an integrative literature review study with a qualitative approach that sought to analyze the applicability and effectiveness of the use of articaine in pediatric dentistry. Articles available in the Scientific Electronic Library Online (SciELO) electronic library were selected, in the Latin American and Caribbean Health Literature database (LILACS) accessed through the Virtual Health Library (VHL) and in the database from PubMed. Results: The studies compared the effectiveness of articaine, in the infiltration technique, compared to lidocaine in BNAI, being equally effective, where the infiltration technique is less painful. However, there is controversy about its use in children under 4 years of age. Conclusion: Articaine is a local anesthetic with rapid action, low toxicity, high potency, and differentiated biotransformation. Showing effectiveness in pediatric dentistry, with appropriate knowledge and techniques.